Oxidative treatment of bromide-containing waters: Formation of bromine and its reactions with inorganic and organic compounds - a critical review - Heeb, M.; Criquet, Justine; Zimmermman-Steffens, S.; von Gunten, Urs (IWA Publishing, 2014)
Bromide (Br-) is present in all water sources at concentrations ranging from ~10 to >1000 µg L-1 in fresh waters and about 67 mg L-1 in seawater. During oxidative water treatment bromide is oxidized to hypobromous acid/hypobromite (HOBr/OBr-) and other bromine species. A systematic and critical literature review has been conducted on the reactivity of HOBr/OBr- and other bromine species with inorganic and organic compounds, including micropollutants.The speciation of bromine in the absence and presence of chloride and chlorine has been calculated and it could be shown that HOBr/OBr- are the dominant species in fresh waters. In ocean waters, other bromine species such as Br2, BrCl, and Br2O gain importance and may have to be considered under certain conditions.HOBr reacts fast with many inorganic compounds such as ammonia, iodide, sulfite, nitrite, cyanide and thiocyanide with apparent second-order rate constants in the order of 104–109 M-1 s-1 at pH 7. No rate constants for the reactions with Fe(II) and As(III) are available. Mn(II) oxidation by bromine is controlled by a Mn(III,IV) oxide-catalyzed process involving Br2O and BrCl.Bromine shows a very high reactivity toward phenolic groups (apparent second-order rate constants kapp ˜ 103–105 M-1 s-1 at pH 7), amines and sulfamides (kapp ˜ 105–106 M-1 s-1 at pH 7) and S-containing compounds (kapp ˜ 105–107 M-1 s-1 at pH 7). For phenolic moieties, it is possible to derive second-order rate constants with a Hammett-s-based QSAR approach with log(k(HOBr/-PhO))=7.8-3.5Sslog(k(HOBr/PhO-))=7.8-3.5Ss. A negative slope is typical for electrophilic substitution reactions.In general, kapp of bromine reactions at pH 7 are up to three orders of magnitude greater than for chlorine. In the case of amines, these rate constants are even higher than for ozone. Model calculations show that depending on the bromide concentration and the pH, the high reactivity of bromine may outweigh the reactions of chlorine during chlorination of bromide-containing waters.